Using English Comic Media to Improve English Reading Comprehension Ability in Viii Grade Students of SMP N 1 Modoinding - Karundeng, Pricillia Margaretha; Rombepajung, Paula A.; Wongkar, Yapi (Program Studi Pendidikan Bahasa Inggris, 2024)
Reading comprehension is one of the most important skills in learning English. In the process of learning English, the ability to read comprehension is an important variable that influences the achievement of learning outcomes according to the KKM in English lessons at SMP/MTs. One of the efforts to overcome students' difficulties in reading comprehension of English is the use of learning media. The researcher is interested in conducting a study entitled